Components Of Training Design Models: The Extent Of Practice By Selected Training Institutions In Malaysia. - Mohammed, Faridah (1995)
An organisation can be defined as a group of people who work together to achieve a set of common goals. This brings us to the fact that organisations cannot exist without people: if they are not at executive or managerial positions, they are definitely down there lower the line and further. These people are employed to be efficient and effective and are expected to contribute significantly towards productivity and quality of the products or services offered by their organisations. Perhaps the most significant investment made by any employer in t he present scenario is in training. Therefore it is essential that a systematic approach t o training design be emphasized. The broad objective of this study was to explore the instructional designs practiced by selected training institution sin Malaysia.More specifically,